Healthy Snacks: Multimodal Critical Discourse Analysis of Traditional Food Brand Corporate Storytelling - Ottman, Olsen; Rahmad, Hari Adi; Yuhendri, Rival (Journal of Pragmatics and Discourse Research, 2023)
This research analyzes how a snack manufacturer uses corporate storytelling on social media to promote healthy eating. The new public health period has developed a market for healthy or well-being-related items. Many firms have emerged to give healthy food options. Social semiotic theory and multimodal critical discourse analysis ask: How do these organizations use corporate stories to make themselves seem superior to their competitors? How do they market healthy, appealing products? How does this marketing encourage healthier product choices? One healthy snack company's corporate story reveal that health discourse colonizes healthy eating for marketing and branding. These companies also claim abstract, symbolic, and commercial health. These company stories may mislead consumers who want to eat healthy into eating less healthful goods.